COOLING-REGIME-CONTROLLED STRUCTURAL EVOLUTION OF RHODIUM-DIFFUSED n-Si MONOCRYSTALS: A WIDE ANGLE XRD STUDY (International Congress on Economics, Management and Business Studies, 2026)
This thesis presents a wide-angle X-ray diffraction study of the cooling-regime-controlled structural evolution of rhodium-diffused phosphorus-doped n-type silicon monocrystals. The main purpose of the work is to analyze how slow and rapid cooling after high-temperature treatment at 1300 °C influence the diffraction response of the silicon matrix. Special attention is focused on the dominant (111)Si reflection, which serves as a sensitive indicator of crystallographic orientation, coherent scattering intensity, and defect-related structural changes. The wide-angle XRD pattern shows that both slow-cooled and rapidly cooled n-Si samples preserve the main monocrystalline silicon structure. However, the intensity and shape of the (111)Si peak differ significantly depending on the cooling regime. The slow-cooled sample demonstrates a higher (111)Si peak intensity and FWHM = 0.163°, indicating stronger coherent scattering from the silicon matrix and a more developed redistribution of Rh-related defect complexes. In contrast, the rapidly cooled sample exhibits a lower peak intensity and FWHM = 0.147°, which can be associated with the retention of nonequilibrium defects, frozen microstrain fields, and local impurity-defect configurations. The obtained results confirm that post-diffusion cooling is an important technological factor controlling the structural state of rhodium-diffused silicon.
Keywords: rhodium-diffused silicon, n-Si, wide-angle XRD, slow cooling, rapid cooling, (111)Si reflection, FWHM, microstrain, defect complexes.